KONTRIBUSI HUKUM ISLAM TERHADAP PEMBANGUNAN HUKUM NASIONAL - Ali Imron Hs (Faculty of Law, Universitas Diponegoro, 2012)
Abstract The establishment of national law should consider the law awareness in the community or refer to the existed law in Islam law that stands as the existed law in the community possesses a strategic position in the national law establishment. The role of Islam law in the forming or establishing of national law could be viewed from two sides, which are firstly, it is viewed from Islam law that is one of the source of national law establishing; and secondly, it is viewed from the side of the use of Islam law as positive law that is specifically applied in certain field. Islam law has provided a great contribution, at least upon the side of the spirit or the soul toward establishment of national law. Spreading Islam law ideologi and istinbath ahkam upon the national law establishment takes the strategic place, compared with the demand of the applying of Islam law that is formalistic. Kata kunci: Hukum Islam, Pembangunan Hukum Nasional, Kontribusi Abstrak Pembangunan hukum nasional harus memperhatikan kesadaran hukum dalam masyarakat atau merujuk pada hukum yang hidup dalam masyarakat. Hukum Islam sebagai hukum yang hidup dalam masyarakat mempunyai posisi yang sangat strategis dalam pembangunan hukum nasional. Peranan hukum Islam dalam pembentukan atau pembangunan hukum nasional dapat dilihat dari dua sisi, yaitu pertama dari sisi hukum Islam sebagai salah satu sumber pembentukan hukum nasional; dan kedua dari sisi diangkatnya hukum Islam sebagai hukum positif yang berlaku secara khusus dalam bidang hukum tertentu. Hukum Islam telah memberikan kontribusi yang sangat besar, paling tidak dari segi ruh atau jiwanya terhadap pembangunan hukum nasional. Membumikan asas-asas hukum Islam dan istinbath ahkam dalam pembangunan hukum nasional menempati posisi yang strategis, dibandingkan tuntutan pemberlakuan hukum Islam yang formalistik Kata kunci: Hukum Islam, Pembangunan Hukum Nasional, Kontribusi